Positioning Belief in the Mid-Seventies - George Palamattam (Journal of Dharma, 1978)
Positioning is an attempt to look at Christian Theology as a whole, and to try to find out where we stand at this partlcular moment of time, and why we are there. But I am afrald, from the tone of the book and from the mood of the times, these very questions lose their basic even e ore we come out of the wonder and dismay and get ourselves positioned, and, I think, the author is making a provision for this phenomenon too.